Egocentric and allocentric memory recall strategies moderate transfer action sentence recognition - Cosimo Tuena; Daniele Di Lernia; Giuseppe Riva; Claudia Repetto; Silvia Serino (Language and Cognition)
Embodied cognition theory proposes that spatial cognition preferences facilitate the simulation of action language. Importantly, spatial cognition relies on either egocentric (body-dependent) or allocentric (body-independent) representations. Research demonstrates that spatial representation proclivity influences the simulation of non-transfer action sentences. However, the impact of individual spatial cognition preferences on transfer action sentence simulation remains unexplored. We administered an egocentric and allocentric memory task and an action sentence recognition task to 37 participants. We used an egocentric–allocentric recall strategy proclivity index to classify participants and employed this metric as a moderator between the transfer perspective (first-person perspective, 1PP vs. third-person perspective, 3PP) and the transfer type (concrete vs. abstract). We found that spatial preferences do not moderate 1PP transfer action sentence recognition. Importantly, we found that egocentric proclivity improves 3PP transfer action sentence recognition and that allocentric proclivity hampers 3PP transfer action sentence recognition. No moderation was found for the transfer type. The study suggests that recognition memory for sentences describing others’ actions is related to body-dependent spatial representations, suggesting a possible link between spatial memory proclivity and action language simulation.